Perbedaan Penerapan Model STAD Dan PBL Dalam Meningkatkan Kemampuan Berpikir Kritis Pada Siswa Sekolah Dasar: The Differences in the Application of the STAD and PBL Models in Enhancing Critical Thinking Skills Among Elementary School Students - Ayu Uswah Munjiah; Rena Komalasari; Millah Fithriyani; Yuyu Yuhana (Sumule Indonesia Publishing, 2026)
Critical thinking skills are the ability of students to analyse, evaluate, and make informed decisions based on available information. These skills are essential for students to gain a deeper understanding of learning materials and to solve problems independently. One effort to develop critical thinking skills is by implementing innovative learning models. This study aims to analyse the differences in the effectiveness of the STAD (Student Teams-Achievement Divisions) and PBL (Problem-Based Learning) models, using a differentiated approach to improve the critical thinking skills of fifth-grade students in Indonesian language subjects. Using a descriptive qualitative approach, data were collected through observation of the learning process, documentation, and literature review. The results show that both learning models have the potential to enhance students' critical thinking skills. However, there are significant differences in how each model accommodates students' diverse learning needs. The differentiated approach within the PBL model proved more effective, as it allows students to actively explore problems, collaborate, and find solutions through critical analysis. This study concludes that the PBL model with a differentiated approach has a greater impact on students' critical thinking development.